Net-stacked hierarchical CdOHF architectures: controllable synthesis and visible-light driven photocatalytic performance. Issue 41 (5th October 2021) - Guo, Yingying; Wang, Chi; Cui, Huihui; Wang, Miao; Sun, Tongming; Tang, Yanfeng
Abstract : Net-stacked hierarchical CdOHF architectures were controllably synthesized, and exhibited high efficiency and selectivity for degrading the cationic dye malachite green (MG) under visible light irradiation. Abstract : Net-stacked hierarchical CdOHF architectures were controllably synthesized via a simple hydrothermal method. The SEM and TEM results show that the hierarchical CdOHF structure is made up of many CdOHF nanobelts. Different pH values and reaction times make the CdOHF feature adjustable structural variations with 1D nanobelts, nanobelt-woven 2D nets and net-stacked 3D hierarchical structures. With a first-order reaction rate constant that was 5 times higher than those of other CdOHF morphologies, the obtained net-stacked hierarchical CdOHF architectures exhibited high efficiency and selectivity for degrading the cationic dye malachite green (MG) under visible light irradiation, for example, the decolorization rate for MG (40 mg L −1 ) solution reached approximately 100% within 30 min. Moreover, the hierarchical CdOHF also displayed good photochemical stability for the degradation of MG after five recycles. The improved photocatalytic efficiency of the 3D net-stacked hierarchical CdOHF is ascribed to the synergistic effects of the porous hierarchical architectures, narrower band gap energy and large BET surface areas. This work provides a simple and feasible strategy for controllable synthesis of 3D hierarchical micro/nanomaterials with high performance, and such inexpensive high-performance hierarchical CdOHF architectures can find potential applications for the degradation of organic dyes.